Challenges and opportunities for human-centered design in CGIAR - Müller, Anna; Steinke, Jonathan; Dorado, Hugo; Keller, Salome; Jiménez, Daniel; Ortiz-Crespo, Berta; Schumann, Charlotte (Elsevier, 2024)
CONTEXT Human-Centered Design (HCD) is an open-ended, iterative, and creative approach to problem solving. HCD is increasingly applied in CGIAR, a global AR4D consortium, to overcome problems with adoption, use, and inclusiveness of innovations. With the current digital transformation in food, land, and water systems HCD is gaining more traction. HCD is a process that can help create solutions that are adopted by users and are more inclusive. But the potential of HCD is strongly influenced by the organizational context that surrounds the design process.